DESAIN DAN UJI COBA MEDIA PEMBELAJARAN INTERAKTIF BERBASIS NEARPOD - Elsa Avrelia Wulandari; Yuni Fatisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
AbstractLess innovative learning media, especially on Chemistry learning, made students uninterested in the learning. This research aimed at producing Nearpod based interactive learning media on Periodic System of the Elements lesson that was valid and practical based on the result of validity test by material and media experts, and practical test by chemistry teacher and students. Research and Development (R&D) method was used in this research with 4D (Define, Design, Development, and Disseminate) development model. This research was administered at State Islamic Senior High School 1 Pekanbaru. The subjects of this research were material and media experts, teachers, and students. The object was Nearpod based interactive learning media on Periodic System of the Elements lesson. The validation result by media and material experts showed that the score was 95% with very valid criterion. The result of teacher practicality test was 95.45% with very practical criterion, and the result of student practicality test was 93.27% with very practical criterion. So that, Nearpod based interactive learning media on Periodic System of the Elements lesson could be used to support the learning.Keywords : Interactive Learning Media, Nearpod, Periodic System of the Elements